Answer:
1. 3 ![m/s^{2}](https://tex.z-dn.net/?f=m%2Fs%5E%7B2%7D)
2. 1.5 ![m/s^{2}](https://tex.z-dn.net/?f=m%2Fs%5E%7B2%7D)
3. 3 seconds
4. 0 ![m/s^{2}](https://tex.z-dn.net/?f=m%2Fs%5E%7B2%7D)
5. 2.2 seconds
Explanation:
(1)
From v= u + at where v is final velocity, u is initial velocity, a is acceleration and t is time.
Making a the subject we have
![a=\frac {v-u}{t}](https://tex.z-dn.net/?f=a%3D%5Cfrac%20%7Bv-u%7D%7Bt%7D)
Substituting u=0 since it’s at rest, v=30m/s and t=10 seconds
a = ![\frac {30-0}{10}=3 m/s^{2}](https://tex.z-dn.net/?f=%5Cfrac%20%7B30-0%7D%7B10%7D%3D3%20m%2Fs%5E%7B2%7D)
(2)
From v= u + at where v is final velocity, u is initial velocity, a is acceleration and t is time.
Making a the subject we have
![a=\frac {v-u}{t}](https://tex.z-dn.net/?f=a%3D%5Cfrac%20%7Bv-u%7D%7Bt%7D)
Substituting u=10m/s, v=22m/s and t=8 seconds
a = ![\frac {22-10}{8}=1.5 m/s^{2}](https://tex.z-dn.net/?f=%5Cfrac%20%7B22-10%7D%7B8%7D%3D1.5%20m%2Fs%5E%7B2%7D)
(3)
From v= u + at where v is final velocity, u is initial velocity, a is acceleration and t is time.
Making t the subject we have
![t=\frac {v-u}{a}](https://tex.z-dn.net/?f=t%3D%5Cfrac%20%7Bv-u%7D%7Ba%7D)
Substituting u=0m/s since at rest, v=15m/s and a=5 ![\frac {m}{s^{2}}](https://tex.z-dn.net/?f=%5Cfrac%20%7Bm%7D%7Bs%5E%7B2%7D%7D)
= ![\frac {15-0}{5}=3s](https://tex.z-dn.net/?f=%5Cfrac%20%7B15-0%7D%7B5%7D%3D3s)
(4)
When initial and final velocity are constant, there’s no acceleration as proven below
From v= u + at where v is final velocity, u is initial velocity, a is acceleration and t is time.
Making a the subject we have
![a=\frac {v-u}{t}](https://tex.z-dn.net/?f=a%3D%5Cfrac%20%7Bv-u%7D%7Bt%7D)
Substituting u=20 since it’s at rest, v=20m/s and t=10 seconds
a = ![\frac {20-20}{10}=0 m/s^{2}](https://tex.z-dn.net/?f=%5Cfrac%20%7B20-20%7D%7B10%7D%3D0%20m%2Fs%5E%7B2%7D)
(5)
From v= u + at where v is final velocity, u is initial velocity, a is acceleration and t is time.
Making t the subject we have
![t=\frac {v-u}{a}](https://tex.z-dn.net/?f=t%3D%5Cfrac%20%7Bv-u%7D%7Ba%7D)
Substituting u=9m/s since at rest, v=0m/s and a=-4.1 ![\frac {m}{s^{2}}](https://tex.z-dn.net/?f=%5Cfrac%20%7Bm%7D%7Bs%5E%7B2%7D%7D)
= ![\frac {0-9}{-4.1}=2.2s](https://tex.z-dn.net/?f=%5Cfrac%20%7B0-9%7D%7B-4.1%7D%3D2.2s)